Introducing good money: Legal tender problem or question of structured approach? - Edo Omerčević (DANUBE: Law, Economics and Social Issues Review, 2014)
The aim of this paper is to theoretically analyse the issues concerning the introduction of alternative moneys. A brief performance evaluation of the current monetary system, as well as two alternatives, namely gold and a private currency, i.e. the Swiss WIR, is followed by a historical look at the relationship between legal tender laws and Gresham's Law. The significance of legal tender laws in introducing alternative moneys is questioned and the focus is shifted to the political and ideological problems. It is pointed out that a professional and structured approach needs to be adopted to successfully introduce monetary substitutes. The derived conclusion is that legal tender laws are not the major factor hindering the introduction of alternative moneys, but that a range of legal, economic and political factors require a dedicated and professional approach to enable the private sector to work on better exchange mechanisms.
Keywords: 330; Money; Legal Tender Law; Private Currency